Cabaran Psikologi bagi Remaja yang Menghidap Diabetes Jenis 1 (Sains Humanika, 2018)
Managing a chronic disease is very challenging and requires effective coping strategies to overcome difficulties for maintaining the health and stability of quality of life. Type 1 diabetes is one of the most common chronic diseases in children and adolescents that requires complex treatment and care. Type 1 diabetes management aspects include insulin intake, checking blood glucose levels, monitoring risk and treatment of disease complications, dietary intake, and physical activity. In addition, the lack of understanding of diabetes among family members and friends also makes them difficult to adapt to the disease and can cause them to experience psychological problems and stress. Hence, this paper aims to identify the psychological challenges faced by children and adolescents with type 1 diabetes. The study is conducted by review the literature on 9 published articles from 2010 to 2017 obtained from the Science Direct, SAGE, PubMed and NIH Public Access. The findings have identified several aspects of psychology often experienced by children and adolescents with type 1 diabetes such as depression, anxiety, stress, and distress. This psychological condition can have a negative effect on life skills, glucose control and ability to deal with diabetes management. It is hoped that proper management in encountering psychological challenges will lead to better results.
Keywords: Psychology; diabetes mellitus; type 1 diabetes; diabetes management; quality of life